Multiple cytokine expression profiles reveal immune-based differences in occult hepatitis B genotype H-infected Mexican Nahua patients - Fierro,Nora Alma (2011)
A high prevalence of occult hepatitis B (OHB) genotype H infections has been observed in the native Mexican Nahua population. In addition, a low incidence of hepatitis B virus (HBV)-associated hepatocellular carcinoma has been described in Mexico. The immune response to infection among OHB-infected patients has been poorly evaluated in vivo. Therefore, we assessed the expression profiles of 23 cytokines in OHB genotype H-infected Nahua patients. A total of 41 sera samples from natives of the Nahua community were retrospectively analysed. Based on their HBV antibody profiles, patients were stratified into two groups: OHB patients (n = 21) and patients that had recovered from HBV infection (n = 20). Herein, we report distinctive cytokines profiles in OHB-infected individuals. Compared to healthy controls (n = 20) and patients who resolved HBV infection, OHB-infected patients displayed an increase in interleukin (IL)-2 secretion in addition to a characteristic inflammation profile (decrease in IL-8 and tumour necrosis factor-alpha levels and increased levels of tumour growth factor-beta). IL-15 and interferon-gamma levels were reduced in OHB-infected individuals when compared to those patients who resolved HBV infection. In contrast, OHB patients showed an increase in monocyte chemoattractant protein (MCP)-1 and MCP-2 compared to healthy controls and patients who resolved HBV infection. These findings suggest that cytokine expression can influence the severity of OHB disease and could lead to new investigation into the treatment of liver and other infectious diseases.